Pengaruh Penggunaan Bahasa Daerah terhadap Keterampilan Berbicara dalam Bahasa Indonesia pada Anak Usia Sekolah Dasar - Febi Febi; Adrias Adrias; Salmaini Safitri Syam (Lembag, 2025)
This study aims to examine the influence of students' dominant use of regional languages on their Indonesian speaking skills. Employing a qualitative approach, data were collected through observations and open-ended questionnaires. The research subjects were fifth- and sixth-grade elementary school students attending TPQ Al-Muhajirin, located in a community where regional languages are predominantly used in daily communication. The findings indicate that students who primarily communicate in regional languages encounter several difficulties when speaking in Indonesian, including challenges in selecting appropriate vocabulary (72.2%), constructing grammatically accurate sentences (36.1%), code-switching between regional languages and Indonesian (86.1%), and a lack of self-confidence when speaking Indonesian (47.2%). In contrast, students who are accustomed to using Indonesian did not experience such challenges. To overcome these difficulties, students adopted various strategies, such as practicing speaking in Indonesian regularly (36.1%), seeking assistance from teachers or peers (55.6%), and engaging with Indonesian-language materials through reading and video content (5.6%). These results suggest that the dominant use of regional languages significantly affects the speaking skills of elementary school-aged children. Consequently, there is a need for more intensive interventions aimed at enhancing students' Indonesian speaking abilities, such as fostering an environment that actively supports the use of Indonesian in daily communication.